Knowledge and practices related to bovine brucellosis transmission amongst livestock workers in Yewa, south-western Nigeria (2013)
Brucellosis is an endemic disease in the animal population in Nigeria and of major public health importance, particularly amongst livestock workers who are ignorant of the risk of Brucella infection. Therefore, to gain insight into the knowledge and practices related to brucellosis transmission amongst livestock holders (LH) and livestock marketers (LM) in Yewa, an international livestock trading centre in south-western Nigeria, we conducted an interview-based study using a cluster sampling technique. In all, a total of 157 respondents comprising 54 LH and 103 LM were interviewed. Two-thirds (69.5%) of the two groups had poor knowledge of brucellosis with no significant difference between them (p = 0.262). Furthermore, consumption of unpasteurised milk, uncooked meat and its products, co-habitation with animals, and poor hygiene were significant risk practices identified as possible means of transfer of Brucella infection from animals to humans amongst these livestock workers (p < 0.05). In conclusion, our findings revealed that poor knowledge and practices related to the consumption of unpasteurised or unboiled dairy products, contaminated beef, and unhygienic practices are factors that will facilitate Brucella infections amongst livestock workers in Nigeria. Therefore, there is a need for more public health enlightenment programmes, as well as implementation of brucellosis control measures in the cattle populations.